Catastrophic health expenditure according to employment status in South Korea: a population-based panel study - Jae Woo Choi; Tae Hyun Kim; Sung In Jang; Suk Yong Jang; Woo-Rim Kim; Eun Cheol Park (BMJ Open)
Objectives Catastrophic health expenditure (CHE) means that the medical spending of a household exceeds a certain level of capacity to pay. Previous studies of CHE have focused on benefits supported by the public sector or high medical cost incurred by treating diseases in South Korea. This study examines variance of CHE in these households according to changes in employment status. We also determine whether a relationship exists according to income level.Design A longitudinal study.Setting We used the Korean Welfare Panel Study (KOWEPS) conducted by the Korea Institute.Participants The data came from 5335 households during 2009–2012.Outcome measure CHE, defined as health expenditures that were 40% greater than the ability of the household to pay.Results Households with people who experienced changes in job status from employed to unemployed (OR 2.79, 95% CI 2.06 to 3.78) or were unemployed with no status change (OR 1.57, 95% CI 1.28 to 1.92) were more likely to incur CHE than those containing people who were consistently employed. In addition, low-income families with members who had either lost a job (OR 3.52, 95% CI 2.44 to 5.10) or were already unemployed (OR 1.67, 95% CI 1.29 to 2.16) were more likely to incur CHE than those with family members with a consistent job.Conclusions Given the insecure employment status of people with low income, they are more likely to face barriers in obtaining needed health services. Meeting their healthcare needs is an important consideration.